Análise da competitividade da amêndoa de castanha de caju brasileira no mercado internacional no período de 1990 a 2007 - Albuquerque, Daniele Passos de Lima (2010)
In the last two decades, Brazil has been losing international market share of cashew nuts (ACC). Given this situation and the economic importance of the product to the state of Ceara, this article aims to analyze the competitiveness of exports of cashew nuts in Brazil during the period of 1990 to 2007. The methodology involves an assessment of the indicators of Revealed Comparative Advantage (VCR), Coverage Rate (CR), export performance (DES), relative position in the market (POS) and the model constant market share (CMS). The indicators analysis was supplemented with the identification of worldwide leading importers and exporters of ACC, verifying opportunities in new markets for Brazil, besides the possible factors influencing the export performance of this. The results of the indicators of Revealed Comparative Advantage and Rate of coverage indicated that Brazil is losing competitiveness in the period analyzed, especially in relation to its two main competitors Vietnam and India, but also presents opportunity for trade expansion of ACC. The Export Performance indicator shows that, for the base year of 1990, there was loss of participation in four of the five main countries of destination. As a result, in three of these destinations, the Brazilian situation is vulnerable, because although still considered competitive, is losing participation in those markets whose demands for ACC are stable or dynamic. The indicator of Relative Position in the Market identified as surplus, Vietnam, India and Brazil, throughout the period of analysis, however, only the first was able to increase his net contribution of trade balance. For the indicator model Constant Market Share (CMS) has defined four sub-periods of analysis, but it was observed between 1990 and 2007, the growth of Brazilian exports of ACC is largely derived from the growth of world trade, because effects destination for exports and competitiveness effects were limiting the growth of exports, despite their positive contributions in some sub-periods. The results of the competitiveness indicators analyzed indicate that even with an increase in Brazilian exports of ACC, Brazil has been losing external competitiveness, given the slow evolution of its exports to the front of its main competitors.